(untitled) (Actual Problems of Mind, 2024)
Informal logic emerged in the late 1970s as an attempt to create a logic that analyses and evaluates the kinds of reasoning people encounter daily. This includes reasoning in political and social discussions, media, advertising, and everyday interpersonal communication. During the early stages of developing informal logic, scholars viewed it as an alternative to formal logic. In the 1990s, this view was clarified: these two logics are not alternatives but complement each other. The paper examines the history of the formation of the informal movement. It aims to identify the historical preconditions that led to the emergence of informal logic. In this regard, the author studies the historical period from the 1950s to the 1990s. The paper identifies two types of preconditions: conceptual and pedagogical. Drawing on the works of Steven Toulmin and Chaim Perelman from the late 1950s, the author highlights the criticism of formal (symbolic, mathematical) logic as a key conceptual precondition. The criticism is that formal logic does not have the tools for analysing reasoning used in real-life situations. From this premise follows the proposal to give logic an empirical character - to develop practical tools for analysing and evaluating real arguments. Another conceptual precondition is to involve informal fallacies in logical consideration, which was convincingly argued in Charles Hamblin’s famous work «Fallacies» (1970). In the paper, the author studies the history of university logic teaching from the 1950s to the 1970s. Summarising, the author states that the dissatisfaction expressed by teachers and students regarding the courses on symbolic logic, along with the appearance of new logic courses and textbooks, played a crucial role in the emergence of the informal initiative.